Implementasi Rakrutmen Calon Pegawai Negari Sipil Di Badan Kapegawaian Daerah Kabupaten Kepulauan Talaud - SILVIA MALUTU; MASJE PANGKEY; JANTJE MANDEY (Universitas Sam Ratulangi, 2014)
The recruitment process is to obtain human resources activities for the benefit of theincrease in public services according to the needs that have been planned in advance. The purpose ofCPNS course to meet in accordance with job vacancies to be filled by reason of the development oforganizations and fulfill vacancies left by his predecessor as occupying retirement, stopping at his ownrequest or dismissed for violating discipline. Politicization of the bureaucracy which often occurs inpolitical parties vying for control of the ministry. It is also an impact to the CPNS recruitment andposition determination is not objective. And problem for the sake of any procurement CPNSrecruitment. Even this is often the case in any civil servant recruitment process in the Talaud Islands.Therefore, it needs to be held more research on the